Sarcoidosis New Perspectives - Shamsadin Athari, Seyyed; Mehrabi Nasab, Entezar (IntechOpen, 2022)
Many people worldwide suffer from sarcoidosis, which can be cured or controlled via immune system modulation and immunotherapy. This book presents a comprehensive overview of sarcoidosis and related aspects. It discusses the cell signaling pathways and molecular mechanisms involved in sarcoidosis as well as pathophysiology, diagnosis, management, and treatment of the disease.